Coupled excitation energy and charge transfer dynamics in reaction centre inspired model systems. (23rd April 2019) - Richter, Martin; Fingerhut, Benjamin P.
Abstract : We present numerical simulations on bacterial reaction centre (bRC) inspired model systems that utilize the recently developed MACGIC-iQUAPI method. Abstract : Functional operation conditions of reaction centre core complexes require the tight coupling of exciton states to concomitant charge separation. Rigorous theoretical treatment of such integrated excitation energy transfer (EET) and charge transfer (CT) dynamics is particularly challenging due to (i) appreciable system sizes, (ii) inter-site and system-bath couplings of similar magnitude that render the Born–Markov approximation invalid, (iii) substantial reorganization energies of CT states, and (iv) the presence of complex structured spectral densities due to vibrational modes of the surroundings. We present numerical simulations on bacterial reaction centre (bRC) inspired model systems that utilize the recently developed MACGIC-iQUAPI method [Richter et al., J. Chem. Phys., 2017, 146, 214101]. The simulations demonstrate that the method provides a rigorous framework for the investigation of such integrated EET–CT dynamics. First, the applicability of the MACGIC-iQUAPI method is explored for a transition from monotonically decaying to oscillatory system-bath influence coefficients, a behavior inherently imposed by structured bath spectral densities. Tightly coupled EET and CT dynamics is further addressed for an excitonic subsystem that resembles strong coupling of special pair states and serves as donor towards a generic bridge–acceptor system. By solving the dissipative quantum dynamics of such bRC inspired model systems, the quenching of excitonic coherence on the hundreds of femtoseconds timescale is explored via a variation of the bridge state energetics, resembling a continuous transition from sequential to superexchange mediated CT regimes. Further, the simulations explore the influence of resonant vibrational modes on the quenching of excitonic coherence via CT. The results reveal a moderate influence of vibrational mode on charge separation dynamics in regimes of biologically relevant EET and CT dynamics.